2012
DOI: 10.1080/19475705.2011.615343
|View full text |Cite
|
Sign up to set email alerts
|

Person-place-time analysis of vehicle fatalities caused by flash floods in Texas

Abstract: A significant number of crashes on roads are caused by adverse weather conditions. Among the most serious consequences of rainfall and flooding in regard to road safety are the motor vehicle-related flash flood fatalities. These fatalities are of particular concern in Texas. Information on motor vehicle fatalities caused by flash floods was extracted from the National Climatic Data Center Storm Data reports. Review of reports on flash flood fatalities in general, where the death circumstances are provided, rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 19 publications
4
39
0
Order By: Relevance
“…Nevertheless, many studies confirm twilight as a dangerous time. In Texas, 55% of motor-related fatalities occurred at night or twilight [26]. Spitalar et al [17] came to the same conclusions on a large sample of flash floods collected in The United States of America.…”
Section: Daily Distributionmentioning
confidence: 68%
See 1 more Smart Citation
“…Nevertheless, many studies confirm twilight as a dangerous time. In Texas, 55% of motor-related fatalities occurred at night or twilight [26]. Spitalar et al [17] came to the same conclusions on a large sample of flash floods collected in The United States of America.…”
Section: Daily Distributionmentioning
confidence: 68%
“…The percentage of car-related flood drownings depends on the country and flood type. In Texas, 80% of flood-related fatalities are motor vehicle-related [26] but, for all the US, the rate announced by French et al [22] was near 40%. It rises to 63% according to a more recent study [27].…”
Section: Different Circumstances Of Deathmentioning
confidence: 99%
“…Total annual and seasonal precipitation has already shifted in some areas of the US, and climate models predict this trend will continue [38] and incidence of severe weather to increase [39, 40]. Determining the impact of recent climate change on road traffic injuries is difficult, given lack of precise exposure information, though the number of deaths in vehicles from flash floods in Texas exhibited a general upward trend from 1959 to 2009 [41]. A study in Vancouver estimated an increase in collision counts by the mid-2050s due to greater rainfall intensity [42].…”
Section: Discussionmentioning
confidence: 99%
“…Over the last years, several activity-based models have been developed: TRANSIMS (Smith et al, 1995), ALBA-TROSS (Arentze and Timmermans, 2000), CEMDAP (Bhat et al, 2004), MATSim (Balmer et al, 2006) and ADAPTS (Auld and Mohammadian, 2009). Although the mentioned models follow the same activity-based paradigm and provide useful frameworks for modeling individual motilities, they have some differences regarding the activity scheduling approach used, the decision-making process integration and the required input data structure.…”
Section: Mobility Modelingmentioning
confidence: 99%
“…Therefore, several vehicle-related accidents occur during flash floods. Death circumstances investigations showed that in postindustrial countries over half of flood victims are motorists trapped by road flooding (Ashley and Ashley, 2007;Sharif et al, 2012;Terti et al, 2017). Hence, daily mobility is pointed out as one of the primary causes of population exposure and vulnerability to flash floods (Ruin, 2010).…”
Section: Introductionmentioning
confidence: 99%